Tourism Communication of Tourism Destinations in the Wetlands of Aranio District Banjar Regency - Lalita Hanief; Achmad Bayu Chandrabuwono; Waluyo, Bambang (LPPM Stikosa - AWS, 2023)
Aranio sub-district has natural tourism potential in the form of mountains, reservoirs, and protected forests. Based on data from preliminary interviews, it is known that one of the natural attractions, namely Pine Island, which is located in Tiwingan Baru, has not been optimally managed because the management has changed. In addition, currently tourist visits to Bukit Batas tours have also dropped dramatically. This research aims to find out the implementation of tourism communication of tourist destinations in the wetlands of Aranio District, Banjar Regency. The method used in this research is descriptive qualitative with data collection techniques in the form of interviews, documentation, and literature studies. The data analysis technique uses Manual Data Analysis Procedure (MDAP), namely daily notes, transcripts, coding, categories, themes, and memos. The results of the study show that tourism communication in Pulau Pinus and Bukit Batu fulfills the components of tourists, marketers, communication, accessibility, human resources and institutions, capital owners and destinations. The media used for promotion through social media instagram, facebook, website and word of mouth marketing. Bukit Batas Tourism is currently unkempt, seen with road access full of weeds.